MORPHOLOGICAL AND MORPHOMETRIC REARRANGEMENTS OF THE RAT ADENOHYPOPHYSIAL-THYROID SYSTEM UNDER THE EXPERIMENTAL EXTRACELLULAR DEHYDRATION - Hryntsova, N.B.; Khomenko, I.V.; Romanyuk, A.M.; Bumeister, V.I.; Kravtsova, I.A. (World of Medicine and Biology, 2019)
Disruption of homeostasis cause significant changes in all the body systems, including the endocrine one. The purpose of the work is to study the morphological and morphometric rearrangements of the adenohypophyseal-thyroid axis in rats under conditions of experimental moderate degree extracellular dehydration. The experiment was performed on 12 rats of control and experimental group. The experimental group's rats for 60 days modeled the moderate degree of extracellular dehydration. Histological, morphometric and statistical methods of investigation were used. Disturbance of the water-salt balance of the body causes a slight increase in secretory activity on the part of adenohypophysis and the development of hypofunction of the thyroid gland, which negatively affects the development of compensatory and adaptive processes in the body.
Keywords: adenohypophysis; extracellular dehydration; thyroid gland; stress